2015
DOI: 10.1111/ldrp.12060
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Children with Learning Disabilities: A Comparison of Self–Reports and Proxy Reports

Abstract: This study aimed to explore how children with learning disabilities (LD) perceive their quality of life (QoL) and to compare self‐reports and proxy reports regarding their QoL. Children with LD, their typically developing peers, their parents and teachers responded to the child, parent, and teacher forms of KINDLR Questionnaire for Measuring Health‐Related Quality of Life (Ravens‐Sieberer & Bullinger, 1998). Findings showed that children with LD reported significantly lower QoL scores than those reported by ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 58 publications
2
22
1
3
Order By: Relevance
“…Esta investigación obtuvo datos de estudiantes con ayudas auditivas de diferentes etapas educativas y sus padres opinando sobre el BcV. En el futuro, convendría comparar dichas percepciones con estudiantes sin dificultades auditivas, como hicieron Warner-Czyz et al También se podría incorporar a los profesores como sujetos que proyectan el BcV de sus alumnos, con objeto de validar el cuestionario KINDL R para maestros, como recomendaron Sakiz, et al (2015). Consideramos que se derivan de este estudio actuaciones vinculadas a estrategias de asesoramiento a familias relacionadas con calidad de vida y con el bienestar físico, emocional, la autoestima y la relación con familia y con los amigos, así como con la escuela de los estudiantes con dificultades auditivas.…”
Section: Resultados De La Concordancia Entre El Kindl R De Niños Y Elunclassified
“…Esta investigación obtuvo datos de estudiantes con ayudas auditivas de diferentes etapas educativas y sus padres opinando sobre el BcV. En el futuro, convendría comparar dichas percepciones con estudiantes sin dificultades auditivas, como hicieron Warner-Czyz et al También se podría incorporar a los profesores como sujetos que proyectan el BcV de sus alumnos, con objeto de validar el cuestionario KINDL R para maestros, como recomendaron Sakiz, et al (2015). Consideramos que se derivan de este estudio actuaciones vinculadas a estrategias de asesoramiento a familias relacionadas con calidad de vida y con el bienestar físico, emocional, la autoestima y la relación con familia y con los amigos, así como con la escuela de los estudiantes con dificultades auditivas.…”
Section: Resultados De La Concordancia Entre El Kindl R De Niños Y Elunclassified
“…Students with special educational needs are motivated to be actively engaged in the learning process, resulting in knowledge gains and better understanding of concepts (Blume et al 2017;Didehbani et al 2016;Freina and Ott 2015;Vasquez III et al 2017), followed by the senses of fulfillment and satisfaction (Rix et al 2009). Self-esteem, self-image, and confidence are positively influenced, as students can see that the above lead to an advancement of their social, emotional, and behavioral status in school (Craig et al 2016;Sakiz et al 2015). Confidence then leads to independence, encouraging them to manifest more behaviors that are acceptable from their peers and teachers (Lan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of individuals with cognitive impairments (especially the ones with ASD), the opportunity of unlimited rehearsals removes their fear of making social mistakes and the anxiety they feel in their face-to-face interactions with others (Didehbani et al 2016;Maskey et al 2014). Quite logically, there is a positive impact on social interactions with peers, self-esteem, self-efficacy, self-image, and confidence, leading to the reduction of social isolation (Craig et al 2016;Sakiz et al 2015). Motivation is also a key feature of VEs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sakız, Sart, Börkan, Korkmaz and Babür (2015) stated that there are advantages to using self-report methods to measure quality of life of children. Research with children has demonstrated that significant correlations between children's self-reports of quality of life and ratings of quality of life by significant others such as parents (Sakız et al, 2015).…”
Section: Findings and Discussionmentioning
confidence: 99%